Dari Etika Domestik ke Etika Kekuasaan: Membaca Qiwa>mah dalam QS. al-Nisa>‘/4:34
This article examines the concept of qiwa>mah in QS. al-Nisa>‘/4:34 by going beyond interpretations that limit it to domestic ethics in husband-wife relationships. Through a qualitative approach based on literature study and semantic-relational analysis, this article shows that qiwa>mah not only functions as a normative status or legitimization of gender hierarchy, but also as an ethical function that arises from certain excess (fad